Optimizing Decision-Making for Placement and Quantity of Tower Cranes in High-Rise Building Projects - Wiratama, Ivan Fahreza; Moengin, Parwadi (Pandawan, 2025)
The optimal placement and selection of tower cranes are critical in high-rise construction projects due to their significant impact on operational efficiency, costs, and safety. Misplacement or an inadequate number of cranes can lead to extended project duration, higher expenses and increased safety risks. This study investigates the factors influencing optimal tower crane placement, evaluates existing methodologies, and introduces a simulation-based approach for enhanced decision-making. Using a case study method, data were collected through site observations, interviews with project managers, and computer simulations. Findings reveal that simulation tools can optimize crane productivity, minimize operational costs, and enhance workplace safety. Integrating advanced technologies such as Building Information Modeling (BIM) further supports accurate placement and operational efficiency. These results underline the importance of leveraging technology to address challenges in high-rise construction management. The study concludes with insights on the generalizability of findings and recommendations for future research, emphasizing real-time monitoring integration.